(untitled) (Journal of Pharmaceutical Negative Results, 2022)
A "learning handicap" is an inexplicable difficulty in gaining fundamental academic abilities in a person of average intelligence. These abilities are necessary for academic and professional success, as well as coping with life in general.Objectives: To determine the level of awareness among primary school teachers on learning disabilities and coping methods prior to the exam. To determine the level of knowledge of learning disabilities and coping methods among primary school instructors after the exam.To compare the degree of awareness of learning disabilities and coping methods among primary school teachers before and after the exam.Methodology: This research adopted quasi experimental (one group pre-test – post-test) research design. The data collecting tool consisted of structured questionnaire to measure primary school teachers' knowledge on learning disabilities and coping strategies that was self-developed and validated by the content experts. Findings: Pre-test levels of learning impairment and coping methods among primary school teachers revealed 91% of them had insufficient awareness, while 8 % had moderately acceptable awareness. The post-test revealed out of 60 teachers, 56 % had adequate knowledge, while 43 % of the teachers showed fairly adequate awareness towards learning disabilities and coping methods. The study's findings indicated a significant difference in instructors' pre- and post-awareness of learning disabilities and coping methods (t= 26.6 at P 0.000).Conclusion: The study findings revealed that the intervention was effective in improving the knowledge on learning disabilities and coping strategies which in turn will improve the overall quality of life of the children with learning disabilities in future.